Microwave-Induced Hearing – its Mechanism and Consequences - Stankiewicz, W.; Krawczyk, A.; Kieliszek, J. (Acta Technica Jaurinensis, 2013)
This paper describes well-documented effect of electromagnetic field at high frequency, i.e. the auditory effect. The history of research in his area is described and some evidences are quoted. The contemporary interpretation of the microwave-induced hearing is discussed as well as new directions of research are drafted.